Effects of rotational thromboelastometry–guided transfusion management in patients undergoing surgical intervention for postpartum hemorrhage: An observational study. Issue 10 (29th August 2021) - Tsang, Yiying (Sally); Kurniawan, Ade Rizki; Tomasek, Owen; Hessian, Elizabeth; Bramley, David; Daly, Oliver; Simons, Koen; Imberger, Georgina
Abstract: Background: Postpartum hemorrhage (PPH) can be associated with coagulopathy, which may be difficult to rapidly assess and may exacerbate blood loss. Rotational thromboelastometry (ROTEM) at the point of care can guide clinician choice of blood products and has been shown in some settings to reduce transfusions and improve outcomes. This hospital‐based observational study aims to measure effects of a ROTEM‐guided transfusion protocol on transfusion practice and clinical outcomes in patients with PPH managed in the operating theater. Study design and methods: We compared a retrospective cohort of 450 consecutive patients with PPH treated in the operating theater before the introduction of a ROTEM‐guided transfusion algorithm in June 2016, with 450 patients treated after its introduction. Multivariate regression was used to evaluate the effect of ROTEM introduction on the primary outcome, patients requiring a packed red blood cell (PRBC) transfusion and adjusting for demographic and obstetric confounders. Secondary outcomes included other blood product transfusions, hysterectomy, and intensive care unit admission. Results: A total of 90 (20%) of patients treated prior to ROTEM introduction received a PRBC transfusion, compared with 102 (22.7%) of those treated after ROTEM introduction (95% confidence interval [CI] 1.0–2.0, p  = .04). There was no difference in PRBC transfusion in patients undergoing caesarean section (95% CI 0.5–1.8, p  = .99). There was a trend toward increased use of cryoprecipitate and reduced use of platelets and fresh frozen plasma after ROTEM introduction. Conclusion: In our institution, the introduction of ROTEM‐guided transfusion did not reduce PRBC transfusion in patients with PPH treated in the operating theater.